The Effect of Group Investigation Learning Model Assisted by Digital Mind Map (GI-DMM) on Student Learning Oucomes in the Cognitive Domain - Afifah, Radhia Silma; Rosba, Evrialiani; Nerita, Siska (Journal Of Biology Education Research (JBER), 2023)
The progress of a nation depends on the quality of education, One way to improve the quality of education is to carry out an effective learning process so as to improve student learning outcomes. learning process the teacher uses a scientific approach, but in learning the scientific approach is implemented not optimally so learning does not involve students actively and learning outcomes are low. Teachers are required to design an innovative learning model that leads to an increase in learning outcomes achieved by students. This research aims to determine the effect of the Group Investigation learning model assisted by Digital Mind Map (GI-DMM) on student learning outcomes in the cognitive domain. This type of research is an experiment with this research design, namely in the experimental class using the application of the Group Investigation learning model assisted by the Digital Mind Map while in the control class it is carried out using a scientific approach, then a final test is carried out on both sample classes.  The determination of the sample was carried out using the Total Sampling technique. The cognitive domain instrument is a test sheet in the form of multiple choice of 39 questions. Data analysis techniques using t-test. The results of this research are based on the t test, the average value of the experimental class is greater than the control class. Thus it can be concluded that through the application of the Group Investigation model it influences learning outcomes in the cognitive domain.